Solid-state battery pole piece, preparation method thereof and solid-state battery

By alternately coating active materials and electrolyte slurry, combined with hot pressing treatment, the problem of poor electrolyte filling effect in all-solid lithium battery electrodes is solved, and the ion conduction efficiency and cycling stability of the battery are significantly improved.

CN119812201AActive Publication Date: 2025-04-11四川新能源汽车创新中心有限公司
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202510163147.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-11
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

In the current electrode preparation process of all-solid lithium batteries, the electrolyte has poor filling effect on the pores of active materials, resulting in low ion conduction efficiency in the battery and poor circulation stability and overall performance.

Method used

The solid-state battery electrode sheet is prepared by alternately coating the active material slurry and the electrolyte slurry. Through the laminated multiple active sheet layers and electrolyte sheet layers, the electrolyte sheets are ensured to fully penetrate and evenly distribute the electrolyte pores, and the structure is cured by hot pressing.

Benefits of technology

It improves the efficiency of ion conduction inside the battery, enhances the cycling stability and overall performance of the battery, and ensures the effective filling of the pores of the active material by the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005271629840000151
    Figure BDA0005271629840000151
  • Figure BDA0005271629840000161
    Figure BDA0005271629840000161
Patent Text Reader

Abstract

The invention provides a solid-state battery pole piece, a preparation method thereof and a solid-state battery, and relates to the field of solid-state batteries. The solid-state battery pole piece comprises a plurality of stacked active piece layers and electrolyte piece layers, wherein the active piece layers and the electrolyte piece layers are alternately arranged; the materials of the active sheet layer comprise a short-range conductive agent, an active material and a first binder, the materials of the electrolyte sheet layer comprise a long-range conductive agent, an electrolyte and a second binder, and the polarity of the first binder is greater than that of the second binder. The solid-state battery pole piece comprises a plurality of active piece layers and electrolyte piece layers, so that electrolyte can be fully permeated and uniformly distributed in active material pores, the ion conduction efficiency in the battery is improved, and the cycling stability and the overall performance of the battery are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of solid-state batteries, and in particular to a solid-state battery pole piece and a preparation method thereof, and a solid-state battery. Background Art

[0002] All-solid-state lithium batteries are considered to be ideal energy storage devices for the next generation of power batteries and energy storage power stations due to their high volumetric energy density and intrinsic safety.

[0003] However, the current electrode preparation process for all-solid-state lithium batteries faces certain challenges. Traditional methods usually use a one-time coating technique to prepare thicker electrode layers. During this process, the electrolyte has a poor filling effect on the pores of the active material. Specifically, due to the complexity of the internal structure of the electrode sheet and the uneven distribution of pores, it is difficult for the electrolyte to fully penetrate and evenly distribute in the pores of the active material, which not only limits the efficiency of ion conduction inside the battery, but may also affect the battery's cycle stability and overall performance.

[0004] Therefore, developing a new solution that can optimize the electrolyte filling effect in the pores inside the electrode is of great significance to improving the comprehensive performance of all-solid-state lithium batteries. Summary of the invention

[0005] The purpose of this application is to provide a solid-state battery electrode, a preparation method thereof, and a solid-state battery to solve the above-mentioned problems.

[0006] To achieve the above objectives, this application adopts the following technical solutions:

[0007] The present application provides a solid-state battery pole piece, comprising a plurality of stacked active sheets and electrolyte sheets, wherein the active sheets and the electrolyte sheets are alternately arranged;

[0008] The material of the active layer includes a short-range conductive agent, an active material, and a first binder. The material forming the electrolyte layer includes a long-range conductive agent, an electrolyte, and a second binder. The polarity of the first binder is greater than that of the second binder.

[0009] As one of many embodiments, the first binder has a dipole moment ≥ 0.45 D, and the second binder has a dipole moment < 0.45 D. For example, the first binder has a dipole moment of 0.45 D, 0.48 D, 0.5 D, 0.6 D, 0.8 D, 1 D, 2 D, 3 D or 4 D, and the second binder has a dipole moment of 0.44 D, 0.42 D, 0.4 D, 0.35 D, 0.3 D or 0.2 D, etc.

[0010] According to an embodiment of the present application, the active material includes a positive electrode active material or a negative electrode active material;

[0011] And / or, the positive electrode active material includes any one of a ternary positive electrode active material and an olivine positive electrode active material, the ternary positive electrode active material includes any one of NCM811, NCM523, and NCM622, and the olivine positive electrode active material includes LiFePO4;

[0012] The negative electrode active material includes at least one of graphite, silicon negative electrode, silicon-carbon negative electrode, and lithium titanate;

[0013] and / or, the particle size of the active material is 0.05-30 μm;

[0014] And / or, the short-range conductive agent includes at least one of SP, KB, and KS-6;

[0015] And / or, the first binder includes at least one of barium phenolic resin, aminophenolic resin, boron phenolic resin, and silicon-modified phenolic resin.

[0016] According to an embodiment of the present application, the mass ratio of the active material to the short-range conductive agent and the first binder is (80-99): (0.5-10): (0.5-10).

[0017] According to an embodiment of the present application, the electrolyte includes Li6PS5Cl, Li 5.5 PS 4.5 Cl 1.5 、Li6PS5Br、Li6PS5I、Li 11 Si2PS 12 , Li 10 SnP2S 12 , Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 10 Ge(P 1-x Sb x )2S 12 , Li 6.6 Ge 0.6 P 0.4 At least one of S5I, where 0.01≤x≤1;

[0018] and / or, the particle size of the electrolyte is 0.01-20 μm;

[0019] And / or, the long-range conductive agent includes at least one of CNTs and VGCF;

[0020] And / or, the second adhesive includes at least one of EPDM rubber, EPDM rubber, butyl rubber, polypropylene resin, and butadiene rubber.

[0021] According to an embodiment of the present application, the mass ratio of the electrolyte to the long-range conductive agent and the second binder is (80-99): (0.5-10): (0.5-10).

[0022] According to an embodiment of the present application, the number of the electrolyte sheet layers is 1-50.

[0023] The present application also provides a method for preparing a solid-state battery electrode as described above, comprising:

[0024] Mixing a short-range conductive agent, an active material, a first solvent, and a first binder to form an active material slurry;

[0025] Mixing a long-range conductive agent, an electrolyte, a second solvent, and a second binder to form an electrolyte slurry;

[0026] coating the active material slurry on the surface of the current collector, performing a first drying, and forming an active material layer on the current collector;

[0027] coating the electrolyte slurry on the surface of the active material layer, performing a second drying, and forming an electrolyte layer on the active material layer;

[0028] The steps of coating the active material slurry, first drying, coating the electrolyte slurry, and second drying are alternately performed to form a plurality of alternating active material layers and electrolyte layers on the current collector, followed by hot pressing to obtain a solid-state battery electrode sheet, wherein the hot pressing treatment causes the active material layer to form an active sheet layer and the electrolyte layer to form an electrolyte sheet layer.

[0029] According to an embodiment of the present application, the first solvent includes at least one of n-butanol, n-hexanol, cyclohexanol, and propylene glycol;

[0030] and / or, the solid content of the active material slurry is 40%-80%;

[0031] and / or, the second solvent comprises at least one of carbon tetrachloride, carbon disulfide, ethyl bromide, ethyl oleate, and isopropyl myristate;

[0032] And / or, the solid content of the electrolyte slurry is 30%-80%;

[0033] and / or, the thickness of the active material layer is 0.05-40 μm;

[0034] And / or, the electrolyte layer has a thickness of 0.01-20 μm.

[0035] According to an embodiment of the present application, the pressure of the hot pressing treatment is 100-500 MPa;

[0036] And / or, the temperature of the hot pressing treatment is 80-150°C;

[0037] And / or, the heat pressing treatment time is 0.5-3h.

[0038] The present application also provides a solid-state battery, which includes the solid-state battery pole piece described above or includes a solid-state battery pole piece prepared by the method for preparing the solid-state battery pole piece described above.

[0039] Compared with the prior art, the beneficial effects of this application include:

[0040] The solid-state battery electrode of the present application includes multiple active layers and electrolyte layers. This structure can ensure that the electrolyte is fully penetrated and evenly distributed in the pores of the active material, which is beneficial to improving the efficiency of ion conduction inside the battery and further improving the cycle stability and overall performance of the battery.

[0041] The present application adopts the method of alternately coating active material slurry and electrolyte slurry to prepare a thicker electrode layer, which can ensure that the electrolyte effectively fills the pores of the active material, effectively improving the cycle stability and overall performance of the battery. DETAILED DESCRIPTION

[0042] As used herein:

[0043] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0044] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0045] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0046] In these examples, parts and percentages are by mass unless otherwise indicated.

[0047] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0048] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0049] Existing methods use a one-time coating technique to prepare thicker electrode layers. During this process, the electrolyte has a poor filling effect on the pores of the active material, resulting in poor battery cycle stability and overall performance.

[0050] In order to improve the above technical problems, the present application provides a solid-state battery pole piece, comprising a plurality of stacked active sheets and electrolyte sheets, wherein the active sheets and the electrolyte sheets are alternately arranged;

[0051] The material of the active sheet layer includes a short-range conductive agent, an active material, and a first binder. The material of the electrolyte sheet layer includes a long-range conductive agent, an electrolyte, and a second binder. The polarity of the first binder is greater than that of the second binder.

[0052] The solid-state battery electrode of the present application includes multiple active layers and electrolyte layers. Such a design can ensure that the electrolyte is fully penetrated and evenly distributed in the pores of the active material, which is beneficial to improving the efficiency of ion conduction inside the battery and further improving the cycle stability and overall performance of the battery.

[0053] According to an embodiment of the present application, the active material includes a positive electrode active material or a negative electrode active material;

[0054] And / or, the positive electrode active material includes any one of a ternary positive electrode active material and an olivine positive electrode active material, the ternary positive electrode active material includes any one of NCM811, NCM523, and NCM622, and the olivine positive electrode active material includes LiFePO4;

[0055] The negative electrode active material includes at least one of graphite, silicon negative electrode, silicon-carbon negative electrode, and lithium titanate;

[0056] and / or, the particle size of the active material is 0.05-30 μm;

[0057] And / or, the short-range conductive agent includes at least one of SP, KB, and KS-6;

[0058] And / or, the first binder includes at least one of barium phenolic resin, aminophenolic resin, boron phenolic resin, and silicon-modified phenolic resin.

[0059] According to an embodiment of the present application, the mass ratio of the active material to the short-range conductive agent and the first binder is (80-99): (0.5-10): (0.5-10).

[0060] For example, the mass ratio of the active material to the short-range conductive agent and the first binder may be 80:10:10, 90:5:5, 99:0.5:0.5 or any value between (80-99):(0.5-10):(0.5-10).

[0061] According to an embodiment of the present application, the electrolyte includes Li6PS5Cl, Li 5.5 PS 4.5 Cl 1.5 、Li6PS5Br、Li6PS5I、Li 11 Si2PS 12 , Li 10 SnP2S 12 , Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 10 Ge(P 1-x Sb x )2S 12 , Li 6.6 Ge 0.6 P 0.4 At least one of S5I, where 0.01≤x≤1;

[0062] and / or, the particle size of the electrolyte is 0.01-20 μm;

[0063] And / or, the long-range conductive agent includes at least one of CNTs and VGCF;

[0064] The short-range conductive agent of the present application adopts a point-shaped conductive agent, and the long-range conductive agent adopts a linear conductive agent. The short-range conductive agent and the long-range conductive agent cooperate with each other, which can not only ensure the conductive effect around the active material, but also improve the long-range conductive performance of the electrode.

[0065] And / or, the second adhesive includes at least one of EPDM rubber, EPDM rubber, butyl rubber, polypropylene resin, and butadiene rubber.

[0066] According to an embodiment of the present application, the mass ratio of the electrolyte to the long-range conductive agent and the second binder is (80-99): (0.5-10): (0.5-10).

[0067] For example, the mass ratio of the electrolyte to the long-range conductive agent and the second binder may be 80:10:10, 90:5:5, 99:0.5:0.5 or any value between (80-99):(0.5-10):(0.5-10).

[0068] According to an embodiment of the present application, the number of the electrolyte sheet layers is 1-50.

[0069] For example, the number of electrolyte sheets can be 1, 10, 15, 20, 25, 30, 35, 40, 45, 50 or any integer between 1 and 50.

[0070] The present application also provides a method for preparing a solid-state battery electrode as described above, comprising:

[0071] Mixing a short-range conductive agent, an active material, a first solvent, and a first binder to form an active material slurry;

[0072] Mixing a long-range conductive agent, an electrolyte, a second solvent, and a second binder to form an electrolyte slurry;

[0073] coating the active material slurry on the surface of the current collector, performing a first drying, and forming an active material layer on the current collector;

[0074] coating the electrolyte slurry on the surface of the active material layer, performing a second drying, and forming an electrolyte layer on the active material layer;

[0075] The steps of coating the active material slurry, first drying, coating the electrolyte slurry, and second drying are alternately performed to form a plurality of alternating active material layers and electrolyte layers on the current collector, followed by hot pressing to obtain a solid-state battery electrode sheet, wherein the hot pressing treatment causes the active material layer to form an active sheet layer and the electrolyte layer to form an electrolyte sheet layer.

[0076] The present application adopts the method of alternately coating active material slurry and electrolyte slurry to prepare a thicker electrode layer, which can ensure that the electrolyte effectively fills the pores of the active material. Specifically, the method of the present application can make the electrolyte fully penetrate and evenly distribute in the pores of the active material, which can effectively improve the efficiency of ion conduction inside the battery, and further improve the cycle stability and overall performance of the battery.

[0077] Usually, the existing method is to directly apply the electrolyte slurry on the active material layer so that the electrolyte is immersed in the active material layer to fill the pores. However, this method easily turns the active material layer into a slurry again, and cannot effectively maintain the spatial structure of the active material layer. The electrolyte slurry cannot fully penetrate into the active material layer. The inventor believes that this is because this method does not take into account that the electrolyte slurry solvent will dissolve the binder in the active material layer. After applying the electrolyte slurry, the solvent in the electrolyte slurry will dissolve the binder in the active material layer, which will cause the electrolyte slurry to be unable to fully penetrate into the active material layer. The solution of the present application can improve this technical problem. Specifically, the first binder with strong polarity in the present application has strong adhesion, and the active material slurry contains the first binder. After the active material slurry is dried, the first binder therein fixes the entire frame, which can ensure the structural stability of the active material layer. Since the polarity of the binder and solvent used in the electrolyte slurry and the active material slurry are different, the first binder in the active material layer will not be dissolved in large quantities when the electrolyte slurry is coated. The present application adopts a solid-liquid contact method, which can effectively fill the electrolyte slurry in the pores of the active material layer, and can effectively improve the problems of long electron ion path of the electrode, uneven electrolyte distribution, high electrode porosity, etc., and can effectively improve the electrode capacity and rate performance.

[0078] Sulfide electrolytes usually react with polar binders and polar solvents. The present application uses a weakly polar second binder and a second solvent when preparing the electrolyte slurry, which are compatible with the sulfide electrolyte. The second binder not only plays an adhesion role but also isolates the sulfide electrolyte from direct contact with the active material layer to produce side reactions. In addition, the second binder has a certain ability to transfer lithium ions, so it does not affect the transmission of lithium ions in the active material layer.

[0079] The electrolyte slurry of the present application has a suitable density and surface tension. After spraying, the electrolyte slurry can better infiltrate into the pores of the active material layer, and the electrolyte and long-range conductive agent therein can better fill and disperse into the pores of the active material layer. After drying the electrolyte slurry, it cooperates with the active material layer to better form a richer and denser conductive electron and ion network, thereby reducing the tortuosity of lithium ion and electron transfer and improving the electrical performance of the electrode.

[0080] The first binder with a strong polarity in the present application will undergo a chemical reaction and solidify and cross-link under a certain pressure and temperature. During the solidification process, the molecular chains are interconnected, and the first binder with a strong polarity will shrink to a certain extent, which can reduce the contact area between the first binder and the active material and reduce the first binder's resistance to the lithium ion transmission of the active material.

[0081] According to an embodiment of the present application, coating includes spraying.

[0082] The active material slurry of the present application can be coated in a dry atmosphere without isolating the air atmosphere, which provides a better operating space and facilitates the scale-up of the process.

[0083] According to an embodiment of the present application, the first solvent includes at least one of n-butanol, n-hexanol, cyclohexanol, and propylene glycol;

[0084] And / or, the active material accounts for 80wt%-99wt% of the total mass of all solid materials in the active material slurry, the short-range conductive agent accounts for 0.5wt%-10wt% of the total mass of all solid materials in the active material slurry, the first binder accounts for 0.5wt%-10wt% of the total mass of all solid materials in the active material slurry, and the solid content of the active material slurry is 40%-80%; wherein all solid materials in the active material slurry are composed of active material, short-range conductive agent, and first binder.

[0085] For example, the solid content of the active material slurry may be 40%, 50%, 60%, 70%, 80%, or any value between 40% and 80%.

[0086] and / or, the second solvent comprises at least one of carbon tetrachloride, carbon disulfide, ethyl bromide, ethyl oleate, and isopropyl myristate;

[0087] And / or, the electrolyte accounts for 80wt%-99wt% of the total mass of all solid materials in the electrolyte slurry, the long-range conductive agent accounts for 0.5wt%-10wt% of the total mass of all solid materials in the electrolyte slurry, the second binder accounts for 0.5wt%-10wt% of the total mass of all solid materials in the electrolyte slurry, and the solid content of the electrolyte slurry is 30%-80%; all solid materials in the electrolyte slurry are composed of electrolyte, long-range conductive agent and second binder.

[0088] For example, the solid content of the electrolyte slurry may be 30%, 40%, 50%, 60%, 70%, 80%, or any value between 30% and 80%.

[0089] and / or, the thickness of the active material layer is 0.05-40 μm;

[0090] For example, the thickness of the active material layer may be 0.05 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, or any value between 0.05-40 μm.

[0091] And / or, the electrolyte layer has a thickness of 0.01-20 μm.

[0092] For example, the thickness of the electrolyte layer may be 0.01 μm, 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, or any value between 0.01 and 20 μm.

[0093] According to an embodiment of the present application, the pressure of the hot pressing treatment is 100-500 MPa;

[0094] For example, the pressure of the hot pressing treatment can be 100 MPa, 150 MPa, 200 MPa, 250 MPa, 300 MPa, 350 MPa, 400 MPa, 450 MPa, 500 MPa or any value between 100 and 500 MPa.

[0095] And / or, the temperature of the hot pressing treatment is 80-150°C;

[0096] For example, the temperature of the hot pressing treatment may be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or any value between 80-150°C.

[0097] And / or, the heat pressing treatment time is 0.5-3h.

[0098] For example, the time of the hot pressing treatment can be 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h or any value between 0.5 and 3 h.

[0099] The present application also provides a solid-state battery, which includes the solid-state battery pole piece described above or includes a solid-state battery pole piece prepared by the method for preparing the solid-state battery pole piece described above.

[0100] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0101] Example 1

[0102] Embodiment 1 provides a solid-state battery electrode, and the preparation method thereof comprises the following steps:

[0103] Preparation of active material slurry: Weigh 5g of graphite negative electrode (D50 particle size is 8μm), 0.625g of SP conductive agent, 0.625g of phenol-formaldehyde resin binder, and 4.1666g of cyclohexanol solvent (solid content is 60%), add the weighed raw materials into a pendulum ball mill and homogenize at 800r / min for 30min to obtain active material slurry.

[0104] Preparation of electrolyte slurry: Weigh 2g of electrolyte Li6PS5Br (D50 particle size is 500nm), 0.25g of VGCF conductive agent, 0.25g of butadiene rubber binder, and 2.5g of ethyl oleate solvent (solid content is 50%), add the weighed raw materials into a pendulum ball mill and homogenize at 1000r / min for 30min to obtain electrolyte slurry.

[0105] The active material slurry is sprayed on the copper foil and dried to form an active material layer on the copper foil. The thickness of the active material layer is 10 μm. Then, the electrolyte slurry is sprayed on the side of the active material layer away from the copper foil and dried to form an electrolyte layer on the active material layer. The thickness of the electrolyte layer is 3 μm.

[0106] The steps of spraying active material slurry, drying, spraying electrolyte slurry and drying are performed alternately to form a plurality of alternating active material layers and electrolyte layers on the copper foil, wherein the number of active material layers and electrolyte layers N is 15. The copper foil is then treated at 200 MPa and 120°C for 1 hour to obtain a solid-state battery electrode.

[0107] Example 2

[0108] Embodiment 2 provides a solid-state battery electrode, and the preparation method thereof comprises the following steps:

[0109] Preparation of active material slurry: Weigh 5g of graphite negative electrode (D50 particle size is 8μm), 0.0252g of SP conductive agent, 0.0252g of boron phenolic resin binder, and 3.367g of propylene glycol solvent (solid content is 60%), add the weighed raw materials into a pendulum ball mill and homogenize at 800r / min for 30min to obtain active material slurry.

[0110] Preparation of electrolyte slurry: Weigh 2g of electrolyte Li6PS5Br (D50 particle size is 500nm), 0.0101g of VGCF conductive agent, 0.0101g of EPDM rubber binder, and 2.0202g of carbon disulfide solvent (solid content is 50%), add the weighed raw materials into a swing ball mill and homogenize at 1000r / min for 30min to obtain electrolyte slurry.

[0111] The active material slurry is sprayed on the copper foil and dried to form an active material layer on the copper foil. The thickness of the active material layer is 15 μm. Then, the electrolyte slurry is sprayed on the side of the active material layer away from the copper foil and dried to form an electrolyte layer on the active material layer. The thickness of the electrolyte layer is 4 μm.

[0112] The steps of spraying active material slurry, drying, spraying electrolyte slurry and drying are performed alternately to form a plurality of alternating active material layers and electrolyte layers on the copper foil, wherein the number of active material layers and electrolyte layers N is 10. The copper foil is then treated at 200 MPa and 120°C for 1 hour to obtain a solid-state battery electrode.

[0113] Example 3

[0114] Embodiment 3 provides a solid-state battery electrode, and the preparation method thereof comprises the following steps:

[0115] Preparation of active material slurry: Weigh 5g of graphite negative electrode (D50 particle size is 8μm), 0.2777g of SP conductive agent, 0.2777g of boron phenolic resin binder, and 3.7037g of propylene glycol solvent (solid content is 60%), add the weighed raw materials into a pendulum ball mill and homogenize at 800r / min for 30min to obtain active material slurry.

[0116] Preparation of electrolyte slurry: Weigh 2g of electrolyte Li6PS5Br (D50 particle size is 500nm), 0.1111g of VGCF conductive agent, 0.1111g of EPDM rubber binder, and 2.2222g of carbon disulfide solvent (solid content is 50%), add the weighed raw materials into a swing ball mill and homogenize at 1000r / min for 30min to obtain electrolyte slurry.

[0117] The active material slurry is sprayed on the copper foil and dried to form an active material layer on the copper foil. The thickness of the active material layer is 15 μm. Then, the electrolyte slurry is sprayed on the side of the active material layer away from the copper foil and dried to form an electrolyte layer on the active material layer. The thickness of the electrolyte layer is 4 μm.

[0118] The steps of spraying active material slurry, drying, spraying electrolyte slurry and drying are performed alternately to form a plurality of alternating active material layers and electrolyte layers on the copper foil, wherein the number of active material layers and electrolyte layers N is 10. The copper foil is then treated at 200 MPa and 100°C for 1.5 hours to obtain a solid-state battery electrode.

[0119] Comparative Example 1

[0120] Comparative Example 1 provides a solid-state battery electrode, and the preparation method thereof comprises the following steps:

[0121] Preparation of active material slurry: Weigh 5g of graphite negative electrode (D50 particle size is 8μm), 0.625g of SP conductive agent, 0.625g of phenol-formaldehyde resin binder, and 4.1666g of cyclohexanol solvent (solid content is 60%), add the weighed raw materials into a pendulum ball mill and homogenize at 800r / min for 30min to obtain active material slurry.

[0122] Preparation of electrolyte slurry: Weigh 2g of electrolyte Li6PS5Br (D50 particle size is 500nm), 0.25g of VGCF conductive agent, 0.25g of phenol-formaldehyde resin binder, and 2.5g of cyclohexanol solvent (solid content is 50%), add the weighed raw materials into a swing ball mill and homogenize at 1000r / min for 30min to obtain electrolyte slurry.

[0123] The active material slurry is sprayed on the copper foil and dried to form an active material layer on the copper foil. The thickness of the active material layer is 10 μm. Then, the electrolyte slurry is sprayed on the side of the active material layer away from the copper foil and dried to form an electrolyte layer on the active material layer. The thickness of the electrolyte layer is 3 μm.

[0124] The steps of spraying active material slurry, drying, spraying electrolyte slurry and drying are performed alternately to form a plurality of alternating active material layers and electrolyte layers on the copper foil, wherein the number of active material layers and electrolyte layers N is 15. The copper foil is then treated at 200 MPa and 120°C for 1 hour to obtain a solid-state battery electrode.

[0125] Comparative Example 2

[0126] Comparative Example 2 provides a solid-state battery electrode, and its preparation method comprises the following steps:

[0127] Preparation of active material slurry: Weigh 5g of graphite negative electrode (D50 particle size is 8μm), 0.0252g of SP conductive agent, 0.252g of phenol-formaldehyde resin binder, and 3.367g of cyclohexanol solvent (solid content is 60%), add the weighed raw materials into a pendulum ball mill and homogenize at 800r / min for 30min to obtain active material slurry.

[0128] Preparation of electrolyte slurry: Weigh 2g of electrolyte Li6PS5Br (D50 particle size is 500nm), 0.0101g of SP conductive agent, 0.0101g of butadiene rubber binder, and 2.0202g of ethyl oleate solvent (solid content is 50%), add the weighed raw materials into a pendulum ball mill and homogenize at 1000r / min for 30min to obtain electrolyte slurry.

[0129] The active material slurry is sprayed on the copper foil and dried to form an active material layer on the copper foil. The thickness of the active material layer is 10 μm. Then, the electrolyte slurry is sprayed on the side of the active material layer away from the copper foil and dried to form an electrolyte layer on the active material layer. The thickness of the electrolyte layer is 3 μm.

[0130] The steps of spraying active material slurry, drying, spraying electrolyte slurry, and drying are performed alternately to form a plurality of alternating active material layers and electrolyte layers on the copper foil, wherein the number of active material layers and electrolyte layers N is 15, and a solid-state battery electrode is obtained.

[0131] Comparative Example 3

[0132] Comparative Example 3 provides a solid-state battery electrode, and the preparation method thereof comprises the following steps:

[0133] Preparation of active material slurry: Weigh 5g of graphite negative electrode (D50 particle size is 8μm), 0.2777g of SP conductive agent, 0.2777g of boron phenolic resin binder, and 3.7037g of propylene glycol solvent (solid content is 60%), add the weighed raw materials into a pendulum ball mill and homogenize at 800r / min for 30min to obtain active material slurry.

[0134] Preparation of electrolyte slurry: Weigh 2g of electrolyte Li6PS5Br (D50 particle size is 500nm), 0.1111g of VGCF conductive agent, 0.1111g of EPDM rubber binder, and 2.2222g of carbon disulfide solvent (solid content is 50%), add the weighed raw materials into a swing ball mill and homogenize at 1000r / min for 30min to obtain electrolyte slurry.

[0135] The active material slurry is sprayed on the copper foil and dried to form an active material layer on the copper foil. The thickness of the active material layer is 15 μm. Then, the electrolyte slurry is sprayed on the side of the active material layer away from the copper foil and dried to form an electrolyte layer on the active material layer. The thickness of the electrolyte layer is 4 μm.

[0136] The steps of spraying active material slurry, drying, spraying electrolyte slurry and drying are performed alternately to form a plurality of alternating active material layers and electrolyte layers on the copper foil, wherein the number of active material layers and electrolyte layers N is 10. The copper foil is then treated at 50 MPa and 60°C for 3 hours to obtain a solid-state battery electrode.

[0137] Electrochemical performance test of solid-state battery pole piece:

[0138] The solid-state battery pole pieces prepared in Examples 1-3 and Comparative Examples 1-3 were assembled into solid-state batteries, and electrochemical performance tests were performed. The specific steps are as follows.

[0139] The solid-state battery pole pieces prepared in the embodiment and the comparative example were used as negative electrodes and cut into small discs with a diameter of 10 mm. 85 mg of LPSC651 was weighed in a glove box and poured into a mold. The mold was pressed twice at a pressure of 300 MPa to obtain a LPSC651 layer. Then, a negative electrode piece was added to one side of the LPSC651 layer. The mold was pressed twice under the same conditions. Then, a 10 mm diameter In piece and a 8 mm lithium piece were added to the side of the LPSC651 layer away from the negative electrode. The mold was sealed and then the mold frame was tightened with a torque wrench to obtain a mold battery.

[0140] The assembled mold battery was placed in a 45°C constant temperature box for 12 hours, and then the negative electrode was subjected to 0.05C and 1C charge and discharge tests at a voltage range of -0.59V-0.9V, and a cycle test at 0.5C. The theoretical specific capacity is 355mAh·g -1 .

[0141] The test results are shown in Table 1 below.

[0142] Table 1 Comparison of electrochemical performance of embodiments and comparative examples

[0143]

[0144]

[0145] As can be seen from Table 1, the specific capacity and cycle performance of Examples 1-3 are significantly higher than those of Comparative Examples 1-3, indicating that the electrochemical performance of the solid-state battery pole pieces prepared in Examples 1-3 is better than that of the solid-state battery pole pieces prepared in Comparative Examples 1-3. This indicates that by controlling the polarity of the first solvent to be greater than the polarity of the second solvent, the polarity of the first binder to be greater than the polarity of the second binder, using a short-range conductive agent to prepare an active material slurry, using a long-range conductive agent to prepare an electrolyte slurry, and performing hot pressing, the capacity and rate performance of the pole piece can be effectively improved.

[0146] In Comparative Example 1, the same solvent type and the same binder type were used in preparing the active material slurry and the electrolyte slurry, and both used polar solvents and polar binders, which resulted in the dissolution of the binder in the active material layer when spraying the electrolyte slurry, and the filling of the solid-liquid method could not be guaranteed. In addition, the polar binder and polar solvent would reduce the ionic conductivity of the electrolyte, thereby reducing the performance of the entire electrode.

[0147] In Comparative Example 2, the same type of conductive agent was used in preparing the active material slurry and the electrolyte slurry, and both used short-range conductive agents, which reduced the electronic conductivity of the electrode. In addition, Comparative Example 2 did not treat the electrode under specific pressure and temperature, resulting in the polar binder not being cured and cross-linked, increasing the contact area between the binder and the active material, and reducing the ionic conductivity.

[0148] In Comparative Example 3, the electrode was processed at a pressure of 50 MPa and a temperature of 60°C. Since the pressure and temperature for processing the electrode were too low, the curing and cross-linking effect of the polar binder was weak, the contact area between the binder and the active material increased, and the ionic conductivity of the active material was reduced.

[0149] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0150] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A solid-state battery electrode, characterized in that: It comprises a plurality of stacked active sheets and electrolyte sheets, wherein the active sheets and the electrolyte sheets are alternately arranged; The material of the active sheet layer includes a short-range conductive agent, an active material, and a first binder. The material of the electrolyte sheet layer includes a long-range conductive agent, an electrolyte, and a second binder. The polarity of the first binder is greater than that of the second binder.

2. The solid-state battery pole piece according to claim 1, characterized in that: The active material includes a positive electrode active material or a negative electrode active material; and / or, the particle size of the active material is 0.05-30 μm; And / or, the short-range conductive agent includes at least one of SP, KB, and KS-6; And / or, the first binder includes at least one of barium phenolic resin, aminophenolic resin, boron phenolic resin, and silicon-modified phenolic resin.

3. The solid-state battery pole piece according to claim 2, characterized in that: The mass ratio of the active material to the short-range conductive agent and the first binder is (80-99): (0.5-10): (0.5-10).

4. The solid-state battery pole piece according to claim 1, characterized in that: The electrolyte includes Li6PS5Cl, Li 5.5 PS 4.5 Cl 1.5 、Li6PS5Br、Li6PS5I、Li 11 Si2PS 12 , Li 10 SnP2S 12 , Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 10 Ge(P 1-x Sb x )2S 12 , Li 6.6 Ge 0.6 P 0.4 At least one of S5I, where 0.01≤x≤1; and / or, the particle size of the electrolyte is 0.01-20 μm; And / or, the long-range conductive agent includes at least one of CNTs and VGCF; And / or, the second adhesive includes at least one of EPDM rubber, EPDM rubber, butyl rubber, polypropylene resin, and butadiene rubber.

5. The solid-state battery pole piece according to claim 4, characterized in that: The mass ratio of the electrolyte to the long-range conductive agent and the second binder is (80-99): (0.5-10): (0.5-10).

6. The solid-state battery pole piece according to any one of claims 1 to 5, characterized in that: The number of the electrolyte sheets is 1-50.

7. A method for preparing a solid-state battery electrode according to any one of claims 1 to 6, characterized in that: include: Mixing a short-range conductive agent, an active material, a first solvent, and a first binder to form an active material slurry; Mixing a long-range conductive agent, an electrolyte, a second solvent, and a second binder to form an electrolyte slurry; coating the active material slurry on the surface of the current collector, performing a first drying, and forming an active material layer on the current collector; coating the electrolyte slurry on the surface of the active material layer, performing a second drying, and forming an electrolyte layer on the active material layer; The steps of coating the active material slurry, first drying, coating the electrolyte slurry, and second drying are alternately performed to form a plurality of alternating active material layers and electrolyte layers on the current collector, followed by hot pressing to obtain a solid-state battery electrode sheet, wherein the hot pressing treatment causes the active material layer to form an active sheet layer and the electrolyte layer to form an electrolyte sheet layer.

8. The method for preparing a solid-state battery electrode according to claim 7, characterized in that: The first solvent comprises at least one of n-butanol, n-hexanol, cyclohexanol, and propylene glycol; and / or, the solid content of the active material slurry is 40%-80%; and / or, the second solvent comprises at least one of carbon tetrachloride, carbon disulfide, ethyl bromide, ethyl oleate, and isopropyl myristate; And / or, the solid content of the electrolyte slurry is 30%-80%; and / or, the thickness of the active material layer is 0.05-40 μm; And / or, the electrolyte layer has a thickness of 0.01-20 μm.

9. The method for preparing a solid-state battery pole piece according to claim 7 or 8, characterized in that: The pressure of the hot pressing treatment is 100-500MPa; And / or, the temperature of the hot pressing treatment is 80-150°C; And / or, the heat pressing treatment time is 0.5-3h.

10. A solid-state battery, characterized in that: The solid-state battery comprises the solid-state battery pole piece according to any one of claims 1 to 6 or comprises a solid-state battery pole piece prepared by the method for preparing a solid-state battery pole piece according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Method for producing all-solid-state battery, and all-solid-state battery

    CN104752774A

  • All-solid-state battery electrode and preparation method and application thereof

    CN111628139A

  • Binder solution for all solid state battery comprising a binder in form of particle and preparing method thereof

    CN113801607A

  • Binder composition, solid-state battery, pole piece slurry of solid-state battery, pole piece and preparation method of solid-state battery

    CN115954478A

  • Solid electrolyte coating for lithium battery, negative pole piece and preparation method of negative pole piece

    CN116014231A